Effects of Thought Suppression on Provoked Men’s Alcohol-Related Physical Aggression in the Laboratory - Gallagher, Kathryn E. (2014)
OBJECTIVE: This study utilized a comprehensive theoretical approach to provide the first data on the impact of thought suppression on provoked men’s alcohol-related aggression. METHOD: A diverse community sample (58% African-American) of males between the ages of 21 and 35 (M = 25.25) were randomly assigned to one of two beverage conditions (i.e., alcohol, no-alcohol control). Following beverage consumption, participants were provoked via reception of electric shocks and a verbal insult from a fictitious male opponent. Participants’ physical aggression was measured using a shock-based aggression task. RESULTS: Results indicated that acute alcohol intoxication significantly increased physical aggression among lower, but not higher, thought suppressing men. CONCLUSIONS: Results suggest that, under conditions of interpersonal provocation, alcohol intoxication produces a myopic focus on hostile thoughts and angry affect in lower, but not higher, suppression men. This pattern of results provides support for the durability of the alcohol myopia effect and highlights the need for continued examination of alcohol’s role in the disruption of protective factors for men’s aggression. It is important for research to continue to identify modifiable cognitive variables that influence self-regulation of behavior; however, it is imperative that researchers consider the extent to which these variables withstand alcohol’s effects.